Circulating Exosomal miRNAs as Novel Biomarkers for Stable Coronary Artery Disease - Yu, Huimin; Yu, Yanhong; Xie, Zhixin; Wu, Tianlong; Wang, Xuan; Chen, Yao; Liang, Tao; Zhang, Ping; Luo, Jianfang (BioMed research international, 2020)
Exosomal miRNAs are currently being explored as a novel class of biomarkers in cardiovascular diseases. However, few reports have focused on the value of circulating exosomal miRNAs as biomarkers for stable coronary artery disease (SCAD). Here, we aimed to investigate whether miRNAs involved in cardiovascular diseases in circulating exosomes could serve as novel diagnostic biomarkers for SCAD. Firstly, the serum exosomes were isolated and purified by the ExoQuick reagent and identified by transmission electron microscopy, western blot, and nanoparticle tracking analysis. Then, the purified exosomes were quantified by measuring the exosome protein concentration and calculating the total protein amount. Next, eight miRNAs involved in cardiovascular diseases, miR-192-5p, miR-148b-3p, miR-125a-3p, miR-942-5p, miR-149-5p, miR-32-5p, miR-144-3p, and miR-142-5p, were quantified in circulating exosomes from the control group (n=20) and the SCAD group (n=20) by quantitative real-time polymerase chain reaction (qPCR). Finally, the gene targets of the differentially expressed miRNAs were predicted, and the functions and signaling pathways of these targets were analyzed using an online database. The isolated exosomes had a bilayer membrane with a diameter of about 100 nm and expressed exosomal markers including CD63, Tsg101, and Flotillin but negatively expressed Calnexin. Both the exosome protein concentration and total protein amount exhibited no significant differences between the two groups. The qPCR assay demonstrated that among the eight miRNAs, the expression levels of miR-942-5p, miR-149-5p, and miR-32-5p in the serum exosomes from the SCAD group were significantly higher than that from the control group. And the three miRNAs for SCAD diagnosis exhibited AUC values of 0.693, 0.702, and 0.691, respectively. GO categories and signaling pathways analysis showed that some of the predictive targets of these miRNAs were involved in the pathophysiology processes of SCAD. In conclusion, our findings suggest that serum exosomal miR-942-5p, miR-149-5p, and miR-32-5p may serve as potential diagnostic biomarkers for SCAD.